Taxonomia e distribuição de Actinocythereis brasiliensis sp. nov. (Podocopida, Trachyleberididae) na plataforma continental brasileira - Machado Cláudia P.; Drozinski Núscia G. S. (Iheringia: Série Zoologia, 2002)
A new species is described, Actinocythereis brasiliensis, from the southern Brazilian continental shelf. It is based on the analysis of 766 samples collected by oceanographical projects. The geographical distribution of this species has revealed its preference by the cold waters and terrigenous sediments and, has a bathymetric distribution between 22 and 164 m but, being concentrated in the shallower waters (< 60 m).